The mammalian oxysterol-binding protein-related proteins (ORPs) bind 25-hydroxycholesterol in an evolutionarily conserved pocket - Suchanek, Monika (Portland Press Ltd., 2007)
OSBP (oxysterol-binding protein) homologues, ORPs (OSBP-related proteins), constitute a 12-member family in mammals. We employed an in vitro [(3)H]25OH (25-hydroxycholesterol)-binding assay with purified recombinant proteins as well as live cell photo-cross-linking with [(3)H]photo-25OH and [(3)H]photoCH (photo-cholesterol), to investigate sterol binding by the mammalian ORPs. ORP1 and ORP2 [a short ORP consisting of an ORD (OSBP-related ligand-binding domain) only] were in vitro shown to bind 25OH. GST (glutathione S-transferase) fusions of the ORP1L [long variant with an N-terminal extension that carries ankyrin repeats and a PH domain (pleckstrin homology domain)] and ORP1S (short variant consisting of an ORD only) variants bound 25OH with similar affinity (ORP1L, K(d)=9.7×10(−8) M; ORP1S, K(d)=8.4 ×10(−8) M), while the affinity of GST–ORP2 for 25OH was lower (K(d)=3.9×10(−6) M). Molecular modelling suggested that ORP2 has a sterol-binding pocket similar to that of Saccharomyces cerevisiae Osh4p. This was confirmed by site-directed mutagenesis of residues in proximity of the bound sterol in the structural model. Substitution of Ile(249) by tryptophan or Lys(150) by alanine markedly inhibited 25OH binding by ORP2. In agreement with the in vitro data, ORP1L, ORP1S, and ORP2 were cross-linked with photo-25OH in live COS7 cells. Furthermore, in experiments with either truncated cDNAs encoding the OSBP-related ligand-binding domains of the ORPs or the full-length proteins, photo-25OH was bound to OSBP, ORP3, ORP4, ORP5, ORP6, ORP7, ORP8, ORP10 and ORP11. In addition, the ORP1L variant and ORP3, ORP5, and ORP8 were cross-linked with photoCH. The present study identifies ORP1 and ORP2 as OSBPs and suggests that most of the mammalian ORPs are able to bind sterols.